Effectiveness of Mental Health Warnings on Tobacco Packaging in People With and Without Common Mental Health Conditions: An Online Randomised Experiment - Sawyer, Katherine; Burke, Chloe; Ng, Ronnie Long Yee; Freeman, Tom P.; Adams, Sally; Taylor, Gemma (Frontiers in Psychiatry, 2022)
Background: Health warning labels on tobacco packaging are a cost-effective means of health risk communication. However, while an extensive range of physical health risks are well-portrayed via current tobacco health warning in the UK, there are none that currently portray the negative impact of smoking on mental health. Aims: i) develop novel mental health warning labels for tobacco packaging and ii) test perceptions of these warnings in smokers and non-smokers, with and without mental health problems. Methods: Six mental health warning labels were developed with a consultancy focus group. These warning labels were tested in an online randomised experiment, where respondents (N = 687) rated six mental health warning labels (MHWLs) and six physical health warning labels (PHWLs) on measures of perceived effectiveness, believability, arousal, valence, acceptability, reactance, novelty of information. Results: MHWLs were perceived as low to moderately effective (mean = 4.02, SD = 2.40), but less effective than PHWLs (mean = 5.78, SD = 2.55, p < .001, ηp2 = 0.63). MHWLs were perceived as less believable, arousing, unpleasant, and acceptable than PHWLs. MHWLs evoked more reactance and were rated as more novel. Perceptions of MHWLs did not differ in people with and without mental health problems except for reactance and acceptability, but consistent with the PHWL literature, perceptions of MHWLs differed between non-smokers and smokers. Conclusions: MHWLs could be an effective means to communicate novel information about the effects of smoking on mental health. MHWLs are perceived as less effective, believable, arousing, unpleasant, and acceptable than PHWLs, but MHWLs evoke more reactance and are rated as more novel.